PENGARUH KOMPOS KIRINYUH (Chromolaena odorata) DAN PUPUK P TERHADAP PERTUMBUHAN DAN HASIL KEDELAI (Glycine max (L) merril) DI LAHAN GAMBUT - Hadi, Muhammad Luqman; Ariani, Erlida (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
The purpose of the experiment was to determine the effect of interaction between the composition of compost and P fertilizer on the growth and yield of soybean crops on peatlands and to get the best combination of treatments. 36 experimental plots measuring    2m x 3m and eight parameters were observed, including relative growth rates, plant height, flowering age, harvest age, percentage of pithy pods, seed yield per m2, weight of 100 seeds and harvest index. This experiment used factorial randomized block design (RBD) method. The results showed a significant increase in compost effect on plant height, harvest age and weight of 100 seeds of soybean plants and P fertilizer application significantly affected harvest age, seed yield per m2 and weight of 100 seeds of soybean plants, but the interaction of the two factors was not significantly different all parameters. The best combination of treatments is by giving 20 tons of ha-1 compost and a 100 kg P P2O5. Ha-1 P fertilizerKeywords:soybean, chromolaena odorata, peat soil